FINANCIAL LITERACY AMONG MILLENNIALS AND ITS RELATIONSHIP WITH FINANCIAL KNOWLEDGE, SKILLS, ATTITUDES AND BEHAVIORS - Damayanti, Umi Rachmah; Nirmala, Ade Ria; Nurani, Ratna (UIN Sunan Gunung Djati Bandung, 2024)
This research aims to determine the level of financial literacy among the millennial generation in Pekanbaru City and understand the influence of financial knowledge, attitudes, and skills on financial behavior. The practical implications of this research are significant, as it can provide insights into how financial literacy can be improved among millennials. This research uses multiple linear regression analysis by conducting reliability and validity tests, classical assumption tests, and hypothesis tests. This type of research is quantitative descriptive research with a sample size of 100 respondents from the millennial generation in Pekanbaru City who have met the sample criteria. The research findings show that financial knowledge, attitudes, and skills positively and significantly affect financial behavior among the millennial generation in Pekanbaru. The coefficient of determination (R2) with an adjusted R square value of 0.876 or 87.6% shows that financial knowledge, attitudes, and skills influence 87.2% of financial behavior. In comparison, the remaining 12.4% is influenced by other variables not used in this research. Therefore, it is hoped that the millennial generation can implement their financial behavior well, not just following trends but considering the benefits they get from every financial decision. It is hoped that the government can also provide education regarding financial management behavior through advertising, social media, or outreach to the public, fostering a hopeful and optimistic future.